A biomimetic approach to improve the dispersibility, interfacial interactions and toughening effects of carbon nanofibers in epoxy composites. (15th March 2017) - Liu, Wanshuang; Wang, Yiru; Wang, Pengfei; Li, Yan; Jiang, Qiuran; Hu, Xiaoyu; Wei, Yi; Qiu, Yiping; Shahabadi, Seyed Ismail Seyed; Lu, Xuehong
Abstract: In this work, the surface of stacked-cup carbon nanofibers (CNFs) was coated with polydopamine (PDA) via a facile biomimetic method based on catecholic chemistry. The modified CNFs (D-CNFs) were incorporated into an epoxy resin in a solvent-free manner. In addition to hydrogen bonding, covalent bonding is also present between amino groups in PDA and epoxy, as verified by Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). Owing to the strong interfacial interactions brought by PDA, D-CNFs show significantly improved dispersibility in epoxy matrix. Consequently, the reinforcing effects of D-CNFs clearly outperform those of pristine CNFs (P-CNFs), especially in terms of fracture toughness. Dynamic thermo-mechanical studies show that the addition of D-CNFs can increase storage modulus more effectively without deteriorating the thermal stability of epoxy matrix. This study confirms that enhancing interfacial interactions in polymer composites by coating nanofillers with PDA is a useful strategy to obtain simultaneous stiffening and toughening in rigid thermoset polymers. Graphical abstract: